and Among Asymptomatic Street Food Vendors in the Dire Dawa city, Eastern Ethiopia: Prevalence, Antimicrobial Susceptibility Pattern, and Associated Factors - Gizaw Tadesse; Habtamu Mitiku; Zelalem Teklemariam; Dadi Marami (SAGE Publishing, 2019)
Background: Salmonella and Shigella infections are a common public health problem throughout the world. The risk of getting infections is high, where asymptomatic street food vendors are preparing foods and vending. Current knowledge of antimicrobial susceptibility pattern is essential for appropriate treatment and management of these infections. Objective: This study was aimed to determine the prevalence, antimicrobial susceptibility pattern, and associated factors of Salmonella and Shigella among asymptomatic street food vendors in the Dire Dawa city, Eastern Ethiopia. Methods: A cross-sectional study was conducted among 218 randomly selected asymptomatic street food vendors in the Dire Dawa city, Eastern Ethiopia from May to July 2017. Data on the sociodemographic and associated factors were collected using a pretested structured questionnaire. The stool specimens collected were examined for Salmonella and Shigella using recommended culture methods. The antimicrobial susceptibility test was done using the disk diffusion technique. Data were described using descriptive statistical tools. Logistic regression models were used to identify the factors associated with Salmonella and Shigella infections. A P -value ⩽ .05 was considered statistically significant. Results: The overall prevalence of Salmonella and Shigella was 8.7% (95% confidence interval: 5.6, 10.3). The most common isolates were Salmonella (6%). Most of the isolates were resistant to amoxicillin (97.7%), ampicillin (89.5%), and tetracycline (68.4%). Almost half (47.4%) of Salmonella isolates were multidrug resistant. Food vendors who did not wash hands with soap after the use of the toilet (adjusted odds ratio: 3.3, 95% confidence interval: 1.2, 7.9), and who had untrimmed fingernails (adjusted odds ratio: 4.4, 95% confidence interval: 1.5, 9.3) had higher odds of Salmonella and Shigella compared with their counterparts. Conclusions: The carrier rate of Salmonella and Shigella was relatively low. Most isolates have developed resistance to amoxicillin, ampicillin, and tetracycline. The odds of Salmonella and Shigella was high among those who lack a habit of hand washing with soap after the use of the toilet and with untrimmed fingernails. Regular screening and appropriate hygienic control measures are needed in place to reduce the risk of infections.